Analysis of lower extremity alignment (LEA) in children with recurrent patellar dislocation by EOS system - Miao, Mingyuan; Cai, Haiqing; Zhang, Li; Cai, Haoqi (Frontiers in Pediatrics, 2023)
Objectives Recurrent patellar dislocation (RPD) greatly affects active young individuals, necessitating the identification of risk factors for a better understanding of its cause. Previous research has connected RPD to lower limb alignment (LEA) abnormalities, such as increased femoral anteversion, tibial external rotation, knee valgus, and flexion. This study aims to use EOS technology to detect RPD-related LEA anomalies, enabling three-dimensional assessment under load conditions. Methods A total of 100 limbs (50 in the RPD group, 50 in the control group) were retrospectively analyzed. In the RPD group, we included limbs with recurrent patellar dislocation, characterized by dislocations occurs at least two times, while healthy limbs served as the control group. We used EOS technology, including 2D and 3D imaging, to measure and compare the following parameters between the two groups in a standing position: Femoral neck shaft angle (NSA), Mechanical femoral tibial angle (MFTA), Mechanical lateral distal femoral angle (mLDFA), Medial proximal tibial angle (MPTA), Anatomical femoral anteversion (AFA), External tibial torsion (ETT), and Femorotibial rotation (FTR). Results The significant differences between the two groups were shown in NSA 3/2D, MFTA 3/2D, mLDFA 3/2D, MPTA 3D, AFA, FTR. No significant difference was shown in MPTA 2D, ETT between the RPD group and the control group. Further binary logistic regression analysis. Further binary logistic regression analysis was conducted on the risk factors affecting RPD mentioned above. and found four risk factors for binary logistic regression analysis: mLDFA (3D), AFA, NSA(3D), and FTR. Conclusions EOS imaging identified abnormal LEA parameters, including NSA, MFTA, mLDFA, MPTA, AFA, and FTR, as risk factors for RPD. Children with these risk factors should receive moderate knee joint protection.